IMPLEMENTASI SIMPLE QUEUE UNTUK MANAJEMEN BANDWIDTH PENGGUNAAN INTERNET (STUDI KASUS : SMK KP BALEENDAH) - Andy Victor Pakpahan (INSTITUT DIGITAL EKONOMI LPKIA, 2023)
Bandwidth usage on a network is often not utilized optimally. This can be caused by the presence of one or more clients that use up bandwidth capacity in the network for downloading and uploading, streaming video, accessing applications that can take up bandwidth capacity. Internet networks, such as in school institutions, often have bandwidth domination between clients. KP Baleendah Vocational School has made extensive use of internet technology. The use of internet technology is carried out to support learning activities as well as activities related to administration. Currently, KP Baleendah Vocational School uses Indihome ISP services with a capacity of up to 100 Mbps. This capacity is used to meet the needs of the laboratory, teacher's room, administration room, and also for students. In the KP Baleendah Vocational School environment, no bandwidth management configuration was found that could accommodate bandwidth allocation to all clients.